Gerhard Giesemann, 2017: Theologie des slowenischen Reformators Primož Trubar - Rajšp, Vincenc (Slavia Centralis, 2021)
The author of the article presents Gerhard Giesemann’s monograph Die Theologie des slowenischen Reformators Primož Trubar (Wien 2017), which was also published in Slovene translation (Teologija Primoža Trubarja). This is the second fundamental work on Primož Trubar, which was published in both languages ​​of Trubar’s preaching work, German and Slovene.